Multiple Cause of Death, 1987 ([Verlag nicht ermittelbar], 1992)
This data collection contains information on all deaths processed by the National Center for Health Statistics for calendar year 1987. Each record in the file includes data on underlying cause and multiple cause of death. Data cover date of death, geographic location (region, state, county, division) of death, residence of the deceased (region, state, county, city, population size), and sex, race, age, marital status, state of birth, origin or descent, kind of business, and occupation of the deceased. The underlying causes of death are coded from the MANUAL OF THE INTERNATIONAL STATISTICAL CLASSIFICATION OF DISEASES, INJURIES, AND CAUSE-OF-DEATH, NINTH REVISION (ICD-9) VOLUMES 1 AND 2.